2022
DOI: 10.1126/sciadv.abl9271
|View full text |Cite
|
Sign up to set email alerts
|

Single-site Pt-doped RuO 2 hollow nanospheres with interstitial C for high-performance acidic overall water splitting

Abstract: Realizing stable and efficient overall water splitting is highly desirable for sustainable and efficient hydrogen production yet challenging because of the rapid deactivation of electrocatalysts during the acidic oxygen evolution process. Here, we report that the single-site Pt-doped RuO 2 hollow nanospheres (SS Pt-RuO 2 HNSs) with interstitial C can serve as highly active and stable electrocatalysts for overall water splitting in 0.5 M H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
125
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(133 citation statements)
references
References 108 publications
8
125
0
Order By: Relevance
“…The electrocatalytic oxygen evolution reaction (OER) is a crucial electrochemical process in energy conversion and storage devices, such as an overall water electrolyzer. The OER was generally operated under three medium: acidic, neutral, and alkaline electrolytes. Among them, both neutral and alkaline water electrolyzer are limited by the electrolyte conductivity, thus just giving a weak current density of less than 0.5 A cm –2 ; by contrast, acidic media in a proton exchange membrane electrolyzer would enable a high current density up to 3 A cm –2 , benefiting to the outcome of high-pressure H 2 (10 MPa) .…”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic oxygen evolution reaction (OER) is a crucial electrochemical process in energy conversion and storage devices, such as an overall water electrolyzer. The OER was generally operated under three medium: acidic, neutral, and alkaline electrolytes. Among them, both neutral and alkaline water electrolyzer are limited by the electrolyte conductivity, thus just giving a weak current density of less than 0.5 A cm –2 ; by contrast, acidic media in a proton exchange membrane electrolyzer would enable a high current density up to 3 A cm –2 , benefiting to the outcome of high-pressure H 2 (10 MPa) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zheng et al designed Pt/LiCoO 2 composite materials with transferable active sites for overall water splitting applications, and the unique structure of heterogeneous interfaces facilitated the adsorption and desorption of reactants 15 . In addition, Wang et al reported that Pt‐doped RuO 2 hollow nanospheres improved the electronic properties of RuO 2 through Pt, thereby achieving the effect of reduced the energy barrier and rapid dissociation of intermediate *O species 16 . However, the mixing of these two materials is not satisfactory due to the poor compatibility 17 .…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, Wang et al reported that Ptdoped RuO 2 hollow nanospheres improved the electronic properties of RuO 2 through Pt, thereby achieving the effect of reduced the energy barrier and rapid dissociation of intermediate *O species. 16 However, the mixing of these two materials is not satisfactory due to the poor compatibility. 17 In addition, the high price of precious metals restricts their large-scale use.…”
Section: Introductionmentioning
confidence: 99%
“…[66] In addition, several nonprecious 1D, 2D, and 3D nano-and microstructured powder catalysts such as MoS 2 , WS 2 , Ni 3 S 2 , NiCo 2 S 4 are also of interest for the HER and OER reactions. [54,[67][68][69][70][71][72][73][74] However, for commercial purposes and practical applica-…”
mentioning
confidence: 99%